Analysis of Conceptual Metaphors Used in British Politicians’ Speeches (Eurasian Research Bulletin, 2022)
Metaphor has a wide range of applications in everyday speech and allows us to communicate our thoughts vividly. The main functions of metaphor in political discourse are heuristic, argumentative, and interactive, smoothing the most dangerous political speech that touches on controversial political issues. This paper reviewed studies on metaphor in political discourse to assess the role of metaphor in politics. Besides, in this article, we investigated conceptual metaphors used in modern political discourses by British politicians and tried to analyse them from a cognitive point of view.